Neuroform Atlas stent deployment through the Barrel vascular reconstruction device for the treatment of a wide-necked acutely ruptured basilar aneurysm. Issue 1 (February 2019) - Valente, Iacopo; D'Argento, Francesco; Alexandre, Andrea; Lozupone, Emilio; Garignano, Giuseppe; Pedicelli, Alessandro
Background: The Barrel vascular reconstruction device is an electrolytically detachable laser-cut closed-cell stent used for neck reconstruction in wide-necked bifurcation aneurysms to support coiling without necessitating dual stent implantation. The purpose is to lower the metal-to-artery ratio and its inherent risk of thromboembolic complications of multiple stents. Case description: A 53-year-old woman presenting with subarachnoid hemorrhage due to acutely ruptured basilar tip aneurysm underwent emergency endovascular embolization with the Barrel vascular reconstruction device. Since the stent did not cover the entire neck of the aneurysm, an Atlas stent was released in a Y configuration through the Barrel. The Neuroform Atlas correctly opened through the Barrel and allowed the complete exclusion of the aneurysm. Conclusion: If necessary, releasing a Neuroform Atlas through a Barrel vascular reconstruction device is a feasible technique.